2009
DOI: 10.1097/sla.0b013e318190a647
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Study of Cholangiocarcinoma With Superficial Spread

Abstract: C(+SS) is associated with less advanced, slower growing tumors and better survival compared with C(-SS). In many cases of C(+SS), the survival does not depend on the complete resection of all the superficial spread but on the stage of the main lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
158
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 153 publications
(166 citation statements)
references
References 29 publications
6
158
2
Order By: Relevance
“…In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not. Thereafter, similar results were reported in Japan,27, 28, 29, 30, 31, 32, 33, 34, 35, 36 the USA,37 South Korea,38, 39 and Germany 40. These findings indicate that discrimination between carcinoma in situ and invasive carcinoma is critical when the ductal resection margins are found to be positive on intraoperative examination of frozen sections; residual carcinoma in situ may lead to late local recurrence, whereas residual invasive carcinoma results in early local recurrence 26…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not. Thereafter, similar results were reported in Japan,27, 28, 29, 30, 31, 32, 33, 34, 35, 36 the USA,37 South Korea,38, 39 and Germany 40. These findings indicate that discrimination between carcinoma in situ and invasive carcinoma is critical when the ductal resection margins are found to be positive on intraoperative examination of frozen sections; residual carcinoma in situ may lead to late local recurrence, whereas residual invasive carcinoma results in early local recurrence 26…”
Section: Introductionsupporting
confidence: 84%
“…26, 27, 28, 31, 32, 34, 35, 38 The reported incidences of complete resection with histopathologically negative margins ranged from 69% to 87% 26, 27, 28, 31, 32, 34, 35, 38. All the studies included in Table 1 confirmed that ductal resection margin status was an independent prognostic factor in patients with extrahepatic cholangiocarcinoma.…”
Section: Biological Behavior Of Residual Carcinoma In Situmentioning
confidence: 80%
See 3 more Smart Citations